Composite dispersion strengthened tungsten alloy and preparation method thereof
By using the pinning of rare earth oxides in W-K alloys, the problem of insufficient recrystallization ability of tungsten alloys during sintering is solved, and the material performance is improved.
Patent Information
- Application Number
- CN202411823631.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The existing tungsten alloys have poor recrystallization capabilities during the high temperature and high temperature stages during the sintering process, resulting in a decline in material performance.
By trace doping rare earth oxides in W-K alloy, combining the pinning of rare earth oxide nanoparticles and K bubbles at different temperatures, the grain boundary diffusion and grain growth are inhibited, thereby broadening the temperature domain of suppressing recrystallization, and a W alloy with fine crystal structure is obtained.
The recrystallization of tungsten alloys is suppressed within a wider temperature range, which improves the overall performance of the material, including a significant improvement in tensile strength.
Smart Images

Figure CN119640077A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of alloy manufacturing, and specifically relates to a composite dispersion strengthened tungsten alloy and a preparation method thereof. Background Art
[0002] Tungsten has the advantages of high melting point, high sputtering threshold, high thermal conductivity, and low tritium retention. It is considered to be the most promising plasma-facing material (PFM) for future fusion reactors. Currently, the International Thermonuclear Experimental Reactor (ITER) and the Hefei Institute of Plasma Physics Institute's Full Superconducting Tokamak Nuclear Fusion Experimental Device (EAST) have selected pure tungsten as the first wall and divertor material. However, there are still many problems to be overcome when using pure tungsten as PFM, including low-temperature brittleness caused by high ductile-to-brittle transition temperature (DBTT) (about 300-500℃), high-temperature embrittlement caused by low recrystallization temperature (RCT) (about 1300℃), and neutron irradiation-induced embrittlement.
[0003] A lot of work has been done internationally to improve the performance of tungsten and tungsten alloys, using a variety of methods including solid solution strengthening, dispersion strengthening, fiber strengthening, fine grain strengthening, etc. Among them, dispersion strengthening has been widely studied, mainly including K doping and rare earth oxide doping.
[0004] K-doped tungsten alloy mainly draws on the strengthening mechanism of doped tungsten wire. Through K, Al, Si and other methods of doping, K will evaporate during the sintering process to form potassium bubbles, and the evaporated potassium bubbles will break into smaller potassium bubbles during the processing process to inhibit grain boundary diffusion and grain growth. Patent (CN109321796A) is based on the above mechanism. Through one or more dopants such as rare earth oxides, tungsten powder, and tungsten carbide, silicon aluminum potassium tungsten powder is obtained after mixing, and then WK alloy with excellent bulk mechanical properties is obtained after cold pressing, sintering, and hot processing. Patent (CN104164579) is based on the potassium bubble strengthening theory. Through discharge plasma sintering, a small-sized block of tungsten with nano potassium bubbles is successfully prepared, which has excellent mechanical properties and heat shock resistance. Foreign fusion material researchers have studied K-doped tungsten plates with K contents of 60 to 220 ppm and found that at a temperature of about 1560°C, potassium aluminum silicate in the K-doped tungsten alloy begins to decompose and produce K bubbles. When the temperature is higher (1900°C), the K element in the potassium aluminum silicate in the alloy material is basically completely decomposed, and most of the K bubbles are pinned on the grain boundaries. As the temperature gradually increases, the number of K bubbles gradually increases. When the temperature rises to 1900-2300°C, its effect in inhibiting the diffusion of grain boundaries and the growth of grains is most significant. When the temperature continues to rise to above 2300°C, the movement of metal atoms intensifies and the pinning effect of K bubbles gradually weakens.
[0005] Rare earth oxides mainly include ThO2, La2O3, Y2O3 and Lu2O3, among which W-La2O3 alloy has excellent performance and has been widely studied. The strengthening mechanism of W-La2O3 alloy is mainly due to the fact that La2O3 is evenly distributed in the tungsten matrix and pinned on the grain boundaries, which can inhibit grain growth by hindering dislocation and grain boundary diffusion. Fusion researchers at home and abroad have conducted extensive research on W with La2O3 content of 0.5-5%, and found that La2O3 has begun to inhibit grain diffusion at lower temperatures (<1200℃). It was found that the hardness of W doped with La2O3 was significantly improved when sintered at higher temperatures (1500-1650℃). When the temperature continues to rise to above 1650℃, the hardness begins to decrease, but it is still higher than the hardness of pure W samples.
[0006] From the above, it can be seen that the prior art has poor ability to inhibit recrystallization in the medium and high temperature stage (1200-1600°C) of WK and the high temperature stage (1600-2300°C) of W-La2O3 alloy during sintering. Therefore, a composite dispersion-strengthened W alloy that inhibits recrystallization of W alloy and a preparation method thereof are needed in the art. Summary of the invention
[0007] Based on the above problems, this scheme aims at satisfying the requirements of fusion reactor operating conditions in all aspects of the performance of plasma-facing materials for fusion reactors, and aims to solve the problem in the background technology that the material performance is degraded due to the recrystallization of sintered WK at medium and high temperatures (1200-1600°C) and W-doped-rare earth oxide alloys at high temperatures (1600-1900°C). By trace-doping rare earth oxides in the WK alloy, the pinning effect of rare earth oxide nanoparticles and K bubbles in different temperature ranges (1200°C-1600°C, 1600°C-1900°C) during the sintering process of the alloy material is combined to inhibit grain boundary diffusion and grain growth, so that the temperature range for inhibiting the recrystallization of the W alloy is wider, and a W alloy with a fine-grained structure is obtained, thereby improving the comprehensive performance of the material.
[0008] To this end, the first technical solution of the present application discloses a method for preparing a composite dispersion strengthened tungsten alloy, comprising the following steps:
[0009] The tungsten-containing compound and the rare earth compound, K2SiO3, Al(NO3)3, and KCl solution are reduced by hydrogen to obtain a mixed alloy powder containing WK and rare earth oxides;
[0010] The mixed alloy powder containing WK and rare earth oxide is pressed, sintered and thermoplastic processed to obtain composite dispersion strengthened tungsten alloy;
[0011] Wherein, the tungsten-containing compound is WO3 or ATM solution, and the rare earth compound is rare earth oxide or soluble rare earth nitrate.
[0012] Furthermore, the added amounts of K2SiO3, Al(NO3)3 and KCl are calculated based on equivalent weights: K content is 0.0006-0.0022wt.%, Si content is 0.0006-0.0009wt.%, and Al addition amount is 0.00008-0.00013wt.%.
[0013] Furthermore, when the rare earth compound is a rare earth oxide, it can be directly mixed with the tungsten-containing compound, K2SiO3, Al(NO3)3, and KCl solution and added, or it can be added after the tungsten-containing compound, K2SiO3, Al(NO3)3, and KCl solution are reduced with hydrogen.
[0014] Furthermore, the rare earth oxides include one or more of La2O3, Y2O3, CeO2, ZrO2 and Tb2O3, and the added amount thereof is 0.063 to 0.63 wt.% of the total mass of WO3.
[0015] Furthermore, the soluble rare earth nitrate includes any one of lanthanum nitrate (La(NO3)3), yttrium nitrate (Y(NO3)3), cerium nitrate (Ce(NO3)3), zirconium nitrate (Zr(NO3)3), and terbium nitrate (Tb(NO3)3), and the added amount thereof is calculated based on the equivalent weight as 0.039-0.396wt.% of WO3 or 0.037-0.37wt.% of AMT.
[0016] Furthermore, the reduction by hydrogen is a step-by-step temperature reduction, the temperature gradients are 300-600°C, 750-850°C, 900-1000°C, the insulation time for each stage is 3-10h, and the hydrogen flow rate is 5-8m 3 / h.
[0017] Furthermore, the pressing pressure is 180-220 MPa, and the holding time is 60-180 s.
[0018] Furthermore, the sintering temperature is 2000-2300° C., the holding time is 5-10 hours, and the atmosphere is hydrogen.
[0019] Furthermore, the hot plastic processing is divided into high-speed forging or rotary forging or rolling process; wherein, the high-speed forging temperature is 1500-1700°C, and forging is performed after keeping warm for 40-80°C, the forging pressure is 30-40MPa, the deformation per pass is 25-35%, and the final deformation is 70%-80%; the rotary forging temperature is 1400-1700°C, keeping warm for 50-70min, the deformation per pass is 28-30%, and the final deformation is 88-94%; the rolling temperature is 1350-1600°C, one hot rolling is used for blanking, and one hot two rolling or one hot three rolling is used subsequently, the roller spacing is reduced by 10-15% between passes, and the insulation between passes is 30-60min, and the final deformation is 78-92%.
[0020] And, the composite dispersion strengthened tungsten alloy prepared according to the above preparation method.
[0021] The present invention has the following beneficial effects:
[0022] The present invention adopts a scheme of doping La2O3 in a WK alloy in a small amount, combines the pinning effect of La2O3 nanoparticles and K bubbles in different temperature ranges (1200°C to 1600°C, 1600°C to 2300°C) during the sintering process of the alloy material to inhibit grain boundary diffusion and grain growth, thereby making the temperature range for inhibiting the recrystallization of the W alloy wider, and obtaining a W alloy with a fine-grained structure, with an average grain size in the range of 2.46 to 3.31 μm.
[0023] Due to the pinning effect of La2O3 particles and K bubbles in the W-La2O3-K alloy, the grain boundary strength of the alloy is synergistically strengthened, and the mechanical properties of the material are significantly improved, with a tensile strength of up to 1373 MPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the metallographic diagram of the sintered state of W-0.05wt.%La2O3-K;
[0025] Figure 2 This is the metallographic diagram of the sintered state of W-0.1wt.%La2O3-K;
[0026] Figure 3 This is the metallographic diagram of the sintered state of W-0.2wt.%La2O3-K;
[0027] Figure 4 This is the metallographic diagram of the sintered state of W-0.5wt.%La2O3-K;
[0028] Figure 5 This is the metallographic diagram of the sintered state of W-0.2wt.%La2O3-K;
[0029] Figure 6 This is the metallographic phase diagram of sintered W-0.2wt.% Y2O3-K. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Unless otherwise specifically stated, the relative arrangement, numerical expressions and numerical values of the parts and steps set forth in these embodiments do not limit the scope of the present application. At the same time, it should be understood that, for ease of description, the sizes of the various parts shown in the accompanying drawings are not drawn according to the actual proportional relationship. The technology, method and equipment known to those of ordinary skill in the relevant field may not be discussed in detail, but in appropriate cases, the technology, method and equipment should be considered as a part of the authorization specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values. It should be noted that similar reference numerals and letters represent similar items in the following drawings, so that once a certain item is defined in an accompanying drawing, it does not need to be further discussed in subsequent drawings.
[0032] To this end, the first embodiment of the present application discloses a method for preparing a composite dispersion strengthened tungsten alloy, comprising the following steps:
[0033] A tungsten-containing compound, a rare earth compound, K2SiO3, Al(NO3)3, and a KCl solution are reduced with hydrogen to obtain a mixed alloy powder containing WK and rare earth oxides; the mixed alloy powder containing WK and rare earth oxides is pressed, sintered, and thermoplastic processed to obtain a composite dispersion-strengthened tungsten alloy; wherein the tungsten-containing compound is WO3 or an ATM solution, and the rare earth compound is a rare earth oxide or a soluble rare earth nitrate.
[0034] In this embodiment, the mixed alloy powder includes WK and rare earth oxides, wherein WK is obtained by hydrogen reduction of a tungsten-containing compound and K2SiO3, Al(NO3)3, and KCl solution, and the rare earth oxide is an actively added rare earth oxide or a soluble rare earth salt obtained by hydrogen reduction; therefore, when the rare earth compound is a rare earth oxide, it can be added before the tungsten-containing compound, K2SiO3, Al(NO3)3, and KCl solution are reduced with hydrogen, or it can be added after the reduction; and when the rare earth compound is a soluble rare earth salt (such as a soluble rare earth nitrate), it needs to be added together with the tungsten-containing compound, K2SiO3, Al(NO3)3, and KCl solution before reduction.
[0035] This embodiment discloses the following preferred addition and reaction methods: Method 1: Mix tungsten oxide with K2SiO3, Al(NO3)3, and KCl solution, and perform hydrogen reduction to obtain WK powder; Add rare earth oxide to the WK powder, and perform mechanical mixing to obtain a mixed alloy powder of WK and rare earth oxide;
[0036] Method 2: Mix tungsten oxide with rare earth oxide and K2SiO3, Al(NO3)3, and KCl solution, and reduce them with hydrogen to obtain WK and rare earth oxide mixed alloy powder;
[0037] Method 3: Mix tungsten oxide, soluble rare earth nitrate, K2SiO3, Al(NO3)3, and KCl solution and reduce them with hydrogen to obtain a mixed alloy powder of WK and rare earth oxide;
[0038] Method 4: AMT solution, soluble rare earth nitrate, K2SiO3, Al(NO3)3, and KCl solution are mixed and reduced by hydrogen to obtain a WK and rare earth oxide mixed alloy powder.
[0039] Among them, ATM solution is ammonium metatungstate (H 28 N6O 41 W 12 , AMT) and water mixed solution, the concentration of ammonium metatungstate is 1.02mol / L (at room temperature).
[0040] In a further embodiment, in the preparation of WK powder, the added amounts of K2SiO3, Al(NO3)3, and KCl are calculated based on equivalent K content of 0.0006-0.0022wt.%, Si content of 0.0006-0.0009wt.%, and Al addition of 0.00008-0.00013wt.%.
[0041] In this embodiment, the rare earth oxides include but are not limited to La2O3, Y2O3, CeO2, ZrO2 and Tb2O3, and the added amount thereof is 0.039-0.396wt.% of WO3 or 0.037-0.37wt.% of AMT based on the total mass of WK powder.
[0042] Furthermore, the soluble rare earth nitrates include but are not limited to lanthanum nitrate (La(NO3)3), yttrium nitrate (Y(NO3)3), cerium nitrate (Ce(NO3)3), zirconium nitrate (Zr(NO3)3), and terbium nitrate (Tb(NO3)3), and the added amount thereof is calculated based on the equivalent weight to be 0.039 to 0.396 wt.% of WO3 or 0.037 to 0.37 wt.% of AMT.
[0043] In this embodiment, the hydrogenation reduction is a step-by-step temperature reduction, the temperature changes are 300-600°C, 700-850°C, 900-1000°C, the insulation time of each stage is 3-10h, and the hydrogen flow rate is 5-8m 3 / h.
[0044] It should be noted that in the above reduction process, the reduction of tungsten oxide is divided into three steps: WO 2.9 →WO 2.72 →WO2→W, different temperatures represent different reduction steps. 300-600℃ is WO 2.9 →WO 2.72 The reduction process of WO 2.72 →WO2 reduction process; 900-1000°C is WO2→W reduction process. Further, the pressing pressure is 180-220MPa, and the holding time is 60-180s.
[0045] Furthermore, the sintering temperature is 2000-2300° C., the holding time is 5-10 hours, and the atmosphere is hydrogen; the relative density of the sintered material is greater than 95%.
[0046] Furthermore, the thermoplastic processing includes (high-speed forging, rotary forging and hot rolling), and any one of the three processes is selected during actual production; wherein the high-speed forging temperature is 1500-1700°C, and forging is performed after keeping warm at 40-80°C, the forging pressure is 30-40MPa, the deformation per pass is 25-35%, and the final deformation is 70%-80%; the rotary forging temperature is 1400-1700°C, and the temperature is kept warm for 50-70min, the deformation per pass is 28-30%, and the final deformation is 88-94%; the hot rolling process temperature is 1350-1500°C, the first blanking adopts one heat and one rolling, and the subsequent one heat and two rolling or one heat and three rolling methods are adopted, and the roller spacing between rolling passes is reduced by 10-15% successively, and the final deformation is 78-92%.
[0047] It should be noted that during the thermoplastic processing, after each heating forging, in order to eliminate residual stress, the forged material should be annealed at 1100-1250℃ for 20-50min.
[0048] The technical effects of the technical solution of the present application will be further described below in conjunction with specific embodiments.
[0049] Example 1
[0050] Preparation of WK powder: Tungsten oxide (WO3) and K2SiO3, Al(NO3)3, KCl solution are used as raw materials, with K content of 0.0001wt.%, Si content of 0.00007wt.%, and Al addition of 0.00009wt.%. After mixing, place in a hydrogen furnace for reduction, heat to 500℃ at 5℃ / min for 3h, then heat to 800℃ at 2.5℃ / min for 8h, and finally heat to 950℃ at 2℃ / min for 8h. The hydrogen flow rate is 6m 3 / h. The average particle size of the WK powder obtained after drying and reduction is 0.7 μm.
[0051] Preparation of W-La2O3-K powder: Add 0.05wt.% La2O3 powder to WK powder, use alcohol as the ball milling medium, mix by ball milling wet mixing, rotate the ball milling tank at 40rad / min, and ball milling time for 24h. After ball milling, dry and obtain W-La2O3-K alloy powder (W-0.05wt.%La2O3-K (100ppm)).
[0052] The W-La2O3-K powder was poured into a rubber mold and pressed in an isostatic press with a pressure of 200 MPa and a holding time of 180 seconds. The pressed green body was sintered in a medium frequency furnace with a sintering temperature of 2100°C and a hydrogen atmosphere with a hydrogen flow rate of 10m 3 / h, holding time 6h, the density is 18.34g / m 3 (relative density is 95.02%), the diameter is 50.37mm, the height is 75.87mm, the metallographic picture of the sintered material is as follows Figure 1 shown.
[0053] Among them, high-speed forging processing: the sintered blank is placed in a hydrogen furnace and heated to 1600℃, kept warm for 50 minutes, and the heated cylinder is forged 3 times with a high-speed hammer, the forging pressure is 40MPa, and the blank is returned to the furnace for heating to 1600℃ and kept warm for 40 minutes between passes. After forging and shaping, a block tungsten alloy material with a relative density of 99.60%, a diameter of 83mm, and a thickness of 8.8mm is obtained.
[0054] Since the high temperature during sintering will cause part of K to volatilize, the actual K content in the bulk tungsten alloy material prepared in this embodiment is 0.00008wt.%.
[0055] Example 2
[0056] The alloy preparation process is the same as that of Example 1, except that the amount of La2O3 powder added is 0.1wt.%.
[0057] The density is 18.38 g / m 3(relative density is 95.24%), the diameter is 51.04mm, the height is 76.17mm, the metallographic diagram of the sintered blank is as follows Figure 2 shown.
[0058] The relative density of the forging billet is 99.71%, the diameter is 84 mm and the thickness is 8.7 mm.
[0059] Since the high temperature during sintering will cause part of K to volatilize, the actual K content in the bulk tungsten alloy material prepared in this embodiment is 0.00008wt.% (82ppm).
[0060] Example 3
[0061] The alloy preparation process is the same as that of Example 1, except that the amount of La2O3 powder added is 0.2wt.%.
[0062] The density is 18.43 g / m 3 (relative density is 95.52%), the diameter is 51.04mm, the height is 76.64mm, the metallographic diagram of the sintered blank is as follows Figure 3 shown.
[0063] The relative density of the forging billet is 99.53%, the diameter is 84 mm and the thickness is 8.6 mm.
[0064] Since the high temperature during sintering will cause part of K to volatilize, the actual K content in the bulk tungsten alloy material prepared in this embodiment is 0.00008wt.% (80ppm).
[0065] Example 4
[0066] The alloy preparation process is the same as that of Example 1, except that the amount of La2O3 powder added is 0.5wt.%.
[0067] The density is 18.42 g / m 3 (relative density is 95.45%), diameter 51.04mm, height 76.17mm, the metallographic image of the sintered material is as follows Figure 4 shown.
[0068] The relative density of the forging billet is 99.65%, the diameter is 84 mm and the thickness is 8.9 mm.
[0069] Since the high temperature during sintering will cause part of K to volatilize, the actual K content in the bulk tungsten alloy material prepared in this embodiment is 0.00008wt.% (79ppm).
[0070] Example 5
[0071] Preparation of W-La2O3-K powder: Mix tungsten oxide, La(NO3)3 with K2SiO3, Al(NO3)3 and KCl solution, with La(NO3)3 accounting for 0.36wt.% of the total mass of tungsten oxide, K content accounting for 0.0001wt.%, Si content accounting for 0.00007wt.%, and Al addition accounting for 0.00009wt.%. After mixing, place in a hydrogen furnace for reduction, heat to 500℃ at 5℃ / min for 3h, then heat to 800℃ at 2.5℃ / min for 8h, and finally heat to 950℃ at 2℃ / min for 8h. The hydrogen flow rate is 6m 3 The W-0.2wt.% La2O3-K powder obtained after drying and reduction had an average particle size of 0.7 μm.
[0072] The W-La2O3-K powder was poured into a rubber mold and pressed in an isostatic press with a pressure of 200 MPa and a holding time of 180 seconds. The pressed green body was sintered in a medium frequency furnace with a sintering temperature of 2100°C and a hydrogen atmosphere with a hydrogen flow rate of 10m 3 / h, holding time 6h, the density is 18.41g / m 3 (Relative density is 95.38%), diameter 50.37mm, height 75.87mm sintered blank, sintered blank metallographic diagram as shown Figure 5 shown.
[0073] Rotary forging: Place the sintered blank in a hydrogen furnace and heat it to 1600℃, keep it warm for 50 minutes, use an air hammer to forge the heated sample to a suitable diameter, put a mold of the corresponding forging size in the rotary forging machine, take out the heated rod, put it in the rotary forging machine to forge half of the length, put it in a molybdenum wire furnace and heat it to 1550℃ after forging, and put it in the rotary forging machine to forge the other half. After multiple forging passes, the deformation of each pass is 28-30%. Between the rolling passes, the material is returned to the furnace and heated to 1550℃ for 50 minutes. The final deformation after forging is 87%. In order to eliminate residual stress, the forged material is annealed at 1100℃ for 20 minutes, and finally a tungsten alloy rod with a diameter of 8mm and a relative density of 99.84% is obtained.
[0074] Since the high temperature during sintering will cause part of K to volatilize, the actual K content in the bulk tungsten alloy material prepared in this embodiment is 0.00008wt.% (81ppm).
[0075] Example 6
[0076] Preparation of W-Y2O3-K powder: AMT solution, soluble rare earth nitrate, K2SiO3, Al(NO3)3, KCl solution were mixed, Y(NO3)3 was 0.32wt.% of the total mass of AMT, K content was 0.000074wt.%, Si content was 0.00005wt.%, Al addition was 0.000064wt.%, and after mixing, it was placed in a hydrogen furnace for reduction, heated to 400℃ at 3℃ / min for 6h, then heated to 800℃ at 2℃ / min for 9h, and finally heated to 950℃ at 2℃ / min for 9h. The hydrogen flow rate was 6m 3 / h. The W-0.2wt.%Y2O3-K powder obtained after drying and reduction has an average particle size of 0.7μm.
[0077] Preparation of sintered compact: The preparation process of sintered compact is the same as that of Example 2. The density is 18.40 g / cm 3 (Relative density is 95.35%), length 187mm, width 147.04mm, thickness 35.5mm sintered blank. The metallographic image of the sintered material is as follows Figure 6 shown.
[0078] Rolling: The sintered billet is kept at 1500℃ for 60min and then hot rolled to open the billet. In the subsequent rolling process, the roller spacing between passes is reduced by 10% successively. After opening the billet, the temperature is lowered to 1400℃ and kept for 50min before rolling for one pass. After the plate is cooled after rolling, the sample is kept at 1400℃ for 50min and then rolled twice. After the plate is cooled after rolling, the plate is kept at 1300℃ for 50min and then rolled three times. After the plate is cooled after rolling, it is annealed at 1100℃ for 30min. Finally, a tungsten alloy plate with a deformation of 80.2%, a thickness of 7mm and a relative density of 99.78% is obtained.
[0079] Since the high temperature during sintering will cause part of K to volatilize, the actual K content in the bulk tungsten alloy material prepared in this embodiment is 0.00008wt.% (78ppm).
[0080] Comparative Example 1
[0081] Preparation of sintered blanks: Add 0.2wt.% La2O3 powder to commercial pure W powder (Xiamen Tungsten Co., Ltd.), use alcohol as the ball milling medium, and mix by wet mixing in ball milling. The speed of the ball milling tank is 40rad / min, and the ball milling time is 24h. After ball milling and drying, W-0.2wt.% La2O3 alloy powder is obtained. Pour the powder into a rubber mold and place it in an isostatic press to form the powder. The pressure is 200MPa and the holding time is 180s. Place the pressed blank in a medium frequency furnace for sintering. The sintering temperature is 2100℃, the atmosphere is hydrogen, and the hydrogen flow rate is 10m 3 / h, holding time 6h, the density is 18.37g / m 3 (Relative density is 95.18%), sintered blank with a diameter of 53.62 mm and a height of 74.87 mm.
[0082] High-speed forging: Same as Example 1. After forging and shaping, a block of tungsten alloy material with a relative density of 99.55%, a diameter of 84.5 mm, and a thickness of 9 mm was obtained.
[0083] Comparative Example 2
[0084] Preparation of sintered blank: blue tungsten oxide, K2SiO3, Al(NO3)3 and KCl solution are used as raw materials, with K content of 0.0001wt.%, Si content of 0.00007wt.%, and Al addition of 0.00009wt.%. After mixing, it is placed in a hydrogen furnace for reduction, heated to 500℃ at 5℃ / min for 3h, then heated to 800℃ at 2.5℃ / min for 8h, and finally heated to 950℃ at 2℃ / min for 8h. The hydrogen flow rate is 6m 3 / h. The average particle size of the powder obtained after drying and reduction is 2μm. The powder is poured into a rubber mold and is pressed in an isostatic press with a pressure of 200MPa and a holding time of 180s. The compact is sintered in a medium frequency furnace with a sintering temperature of 2100℃, a hydrogen atmosphere, and a hydrogen flow rate of 10m 3 / h, holding time 6h, the density is 18.34g / m 3 (Relative density is 95.02%), sintered blank with a diameter of 52.19 mm and a height of 75.24 mm.
[0085] High-speed forging: Same as Example 1. After forging and shaping, a block of tungsten alloy material with a relative density of 99.35%, a diameter of 84 mm, and a thickness of 9 mm was obtained.
[0086] Since the high temperature during sintering will cause part of K to volatilize, the actual K content in the bulk tungsten alloy material prepared in this embodiment is 0.00008wt.% (78ppm).
[0087] Comparative Example 3
[0088] Preparation of sintered blank: Pour commercial pure W powder (Xiamen Tungsten Co., Ltd.) into the rubber mold and place it in an isostatic press to form the mold. The pressure is 200 MPa and the holding time is 180 seconds. The pressed blank is sintered in an intermediate frequency furnace at a sintering temperature of 2100°C, the atmosphere is hydrogen, and the hydrogen flow rate is 10m 3 / h, holding time 6h, the density is 18.10g / m 3 (Relative density is 93.5%), sintered blank with a diameter of 52.19 mm and a height of 75.24 mm.
[0089] The comparison of the average grain size and tensile strength of the bulk tungsten alloy prepared in Examples 1-6 and Comparative Examples 1-3 is shown in Table 1 below.
[0090] Table 1 Composition and performance data of examples and comparative examples
[0091]
[0092] Table 1 The average grain size of the alloys prepared in Examples 1 to 6 and Comparative Examples 1 to 3 was measured with reference to the standard "GB / T6394-2017 Method for Determination of Average Grain Size of Metals":
[0093] Table 1 The tensile strength and elongation test of Examples 1 to 6 and Comparative Examples 1 to 2 were tested with reference to the standard "GB / T 228.2-2015 Tensile test of metallic materials Part 2: High temperature test method", and the tensile test method was selected.
[0094] Result analysis: From the data in Table 1, it can be seen that in the sintered state, the alloys prepared in Examples 1 to 6 have smaller grain sizes than those in Comparative Examples 1 to 3; after thermoplastic processing, the alloys prepared in Examples 1 to 6 have higher tensile strength and better elongation than those in Comparative Examples 1 to 3.
[0095] The above embodiments are only preferred embodiments of the present application, and the scope of implementation of the present application is not limited thereto. The embodiments and features in the embodiments of the present invention can be arbitrarily combined with each other without conflict. Any technician familiar with the technical field can easily think of changes or replacements within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.
Claims
1. A method for preparing a composite dispersion strengthened tungsten alloy, characterized in that: The steps include: The tungsten-containing compound and the rare earth compound, K2SiO3, Al(NO3)3, and KCl solution are reduced by hydrogen to obtain a mixed alloy powder containing WK and rare earth oxides; The mixed alloy powder containing WK and rare earth oxide is pressed, sintered and thermoplastic processed to obtain composite dispersion strengthened tungsten alloy; Wherein, the tungsten-containing compound is WO3 or ATM solution, and the rare earth compound is rare earth oxide or soluble rare earth nitrate.
2. The preparation method according to claim 1, characterized in that: The added amounts of K2SiO3, Al(NO3)3 and KCl are calculated based on equivalent weights, wherein the K content is 0.0006-0.0022wt.%, the Si content is 0.0006-0.0009wt.%, and the Al addition amount is 0.00008-0.00013wt.%.
3. The preparation method according to claim 1, characterized in that: When the rare earth compound is a rare earth oxide, it can be directly mixed with the tungsten-containing compound, K2SiO3, Al(NO3)3, and KCl solution and added, or it can be added after the tungsten-containing compound, K2SiO3, Al(NO3)3, and KCl solution are reduced with hydrogen.
4. The preparation method according to claim 1 or 3, characterized in that: The rare earth oxides include one or more of La2O3, Y2O3, CeO2, ZrO2 and Tb2O3, and the added amount thereof is 0.063-0.63wt.% of WO3.
5. The preparation method according to claim 1, characterized in that: The soluble rare earth nitrate includes any one of lanthanum nitrate, yttrium nitrate, cerium nitrate, zirconium nitrate and terbium nitrate, and the addition amount thereof is 0.039-0.396wt.% of WO3 or 0.037-0.37wt.% of AMT according to the equivalent calculation.
6. The preparation method according to claim 1, characterized in that: The reduction by hydrogen is a step-by-step temperature reduction, the temperature gradients are 300-600°C, 750-850°C, 900-1000°C, the insulation time of each stage is 3-10h, and the hydrogen flow rate is 5-8m 3 / h.
7. The preparation method according to claim 1, characterized in that: The pressing pressure is 180-220 MPa, and the holding time is 60-180 s.
8. The preparation method according to claim 1, characterized in that: The sintering temperature is 2000-2300° C., the holding time is 5-10 hours, and the atmosphere is hydrogen.
9. The preparation method according to claim 1, characterized in that: The hot plastic processing is divided into high-speed forging, rotary forging or rolling process; wherein, the high-speed forging temperature is 1500-1700°C, and forging is performed after keeping warm for 40-80°C, the forging pressure is 30-40MPa, the deformation amount per pass is 25-35%, and the final deformation amount is 70%-80%; the rotary forging temperature is 1400-1700°C, and the temperature is kept warm for 50-70min, the deformation amount per pass is 28-30%, and the final deformation amount is 88-94%; the rolling temperature is 1350-1600°C, one hot rolling is adopted for blanking, and one hot two rolling or one hot three rolling is adopted subsequently, the roller spacing is reduced by 10-15% between passes, and the temperature is kept warm for 30-60min between passes, and the final deformation amount is 78-92%.
10. The composite dispersion strengthened tungsten alloy prepared according to any one of the preparation methods of claims 1-9.
Citation Information
Patent Citations
Method for preparing rare-earth oxide dispersion strengthened fine-grained tungsten material
CN105518169A
Method for preparing high-density ultrafine-grained rare earth oxide doped tungsten alloy
CN110560700A
Preparation method of high-performance tungsten-rhenium thermocouple wire
CN113604719A
Preparation method of high-strength superfine tungsten alloy wire for cutting
CN114888292A
Tungsten-potassium alloy and preparation method and application thereof
CN115958200A